Self-Repair in Tigrinya: Trouble Sources, Mechanisms and Solutions - Mache Asgede, Dagnew (Dialogue and discourse, 2024)
This paper analyzes conversational self-repair, which refers to reconstructing problematic portions of a prior oral discourse by oneself, in Tigrinya. Tigrinya is a Northern Ethio-Eritrean-Semitic language spoken by the inhabitants of the Tigray regional state of Ethiopia and Eritrea. This article relies on recorded oral data from speakers of the Rayya Tigrinya variety, particularly inhabitants of Neksege located to the West of Maichew. A conversational analysis (CA) approach is used to analyze the trouble sources, mechanisms (initiators), and results of self-repair. The article shows that pronunciation problems emanating from dialectal variation or tongue slip, wrong word order including focus misplacement, missing constituents, perceived misunderstandings, and using (totally) wrong constituents are some of the trouble sources that push speakers to repair portions of a prior oral utterance. On top of that, cut-offs, particles, and lexemes (one verbal noun and some predicates) are identified as self-repair initiators. Though cut-offs do not indicate a self-repair, particles and predicates may sometimes indicate a self-repair. Finally, the article posits that expanding, replacing, re-ordering, aborting and restarting, and inserting are some of the solutions set for the repairable segments in the repaired portions of the oral discourse. The author recommends for further investigation repair in the process of language acquisition and learning, and the relationship between self-repair and the demographic features of participants.